Financial Market Integration in a Wider European Union - Corneliu Stirbu (Hamburg Institute of International Economics (HWWA), 2004)
EU enlargement rests on the proven success of European unification. European monetary integration and the introduction of euro are probably the best examples of integration. The EU financial sector has been going through a large restructuring program in the last decades. There was a continuous wave of deregulation since the late 1980s, when the Single Market programme with minimal harmonisation and home country control was implemented in successive periods for banking, insurance and the securities markets. The accession of new members poses huge challenges on the European Union and the countries from Central and Eastern Europe (CEEC). Similarities in economic histories and experiences, as well as comparable methods applied to build the market economies, led to creation of analogous structures and institutions in the CEEC. This was also true for the development of the financial sector. The paper will then investigate the most important characteristics of the financial architecture and will analyse the impact of closer integration of financial sectors in CEEC and EU countries. It will briefly review the developments which have taken place in the financial sector of both groups of countries to provide the background for the later analysis of the expected effects of integration in both old and new member states. Furthermore, it will make a formal assessment of the actual increase in financial market.
Keywords: F36; P34; G15; G2; 330; Financial Aspects of Economic Integration; Financial Institutions and Services; European Financial Markets; Financial Economics; Finanzsektor; Internationaler Finanzmarkt; Marktintegration; EU-Binnenmarkt; EU-Erweiterung; EU-Staaten; Osteuropa